Data base of Variability in resting heart rate in older women practicing Tai Chi Chuan versus non-exercising controls: a cross-sectional comparative study - Pereira, Lucas Camilo (2026)
PURPOSE: The study compared Resting Heart Rate Variability (HRV) in elderly women practicing Tai Chi Chuan (TCC) versus non-exercising controls to evaluate its impact on heart autonomic modulation. METHODOLOGY: Twenty elderly women were allocated into two groups: TCC practitioners (n=10) and non-exercising controls (n=10). The groups were similar in baseline characteristics, including age (TCC: 64.6 ± 3.3 yrs; control: 66.5 ± 7.3 yrs), body mass (TCC: 60.8 ± 4.3 kg; control: 65.5 ± 12.1 kg), height (TCC: 1.52 ± 0.07 m; control: 1.50 ± 0.05 m), and BMI (TCC: 26.2 ± 2.7 kg/m2; control: 28.9 ± 4.3 kg/m2). HRV was assessed using a heart rate monitor and symbolic analysis, focusing on 0V% (sympathetic activity) and 2ULV% (parasympathetic activity). RESULTS: For sympathetic modulation (0V%), the TCC group exhibited significantly lower values at moment 1 (TCC: 28.7 ± 7.9 vs. control: 41.6 ± 8.6, p = 0.003, 95%CI: -20.74 to -5.07; d = -1.56) and moment 2 (TCC: 27.0 ± 12.0 vs. control: 38.9 ± 11.7, p = 0.038, 95%CI: -23.09 to -0.72; d = -1.00), indicating reduced sympathetic dominance among TCC practitioners. In contrast, parasympathetic modulation (2ULV%) was significantly higher in the TCC group at moment 1 (TCC: 13.9  ± 3.5 vs. control: 10.6  ± 2.5, p = 0.032, 95%CI: 0.31 to 6.17; d = 1.08) and moment 2 (TCC: 14.4  ± 3.5 vs. control: 10.5  ± 3.3, p = 0.021, 95%CI: 0.67 to 7.21; d = 1.15). CONCLUSION: The findings highlight the benefits of regular TCC practice, demonstrating its potential to enhance parasympathetic activity and reduce sympathetic activity, thus contributing to autonomic balance and possible cardiovascular protection. Despite limitations like the small sample size and cross-sectional design, TCC is identified as a promising non-pharmacological intervention for cardiovascular health improvement in elderly women, with symbolic analysis effectively capturing patterns of autonomic regulation.